The role of comprehensive education in anti-doping policy legitimacy and support among clean athletes. (May 2022) - Barkoukis, Vassilis; Mallia, Luca; Lazuras, Lambros; Ourda, Despoina; Agnello, Sara; Andjelkovic, Marija; Bochaver, Konstantin; Folkers, Dirk; Bondarev, Dmitriy; Dikic, Nenad; Dreiskämper, Dennis; Petróczi, Andrea; et al.
Abstract: Objectives: Anti-doping policies represent a group of regulations and procedures that are applied by anti-doping organizations in order to safeguard sports against doping. Evidence implies that, for anti-doping policies to be effective, they need to be endorsed by athletes. Still, there is scarce evidence on the process through which athletes decide to endorse and support anti-doping policies and the role of anti-doping education. The main objective of the study was to empirically examine a behavioural model of active anti-doping policy support. Methods: A self-reported survey with measures of perceived anti-doping legitimacy, social support via expected obedience, perceived trustworthiness and social cognitive variables associated with anti-doping policy support (attitudes, social norms, descriptive norms, perceived behavioural control, regret, and intention) was completed by 1328 competitive athletes in 6 countries (Germany, Greece, Italy, Russia, Serbia, UK). Results: Athletes who live in countries with comprehensive (emphasis on individual development and competency with a focus on sport and personal integrity) anti-doping education (ADE) and had received ADE are more supportive of anti-doping policies than athletes from countries with basic education provision anti-doping education (information type education). Furthermore, athletes who received ADE reported significantly higher levels of perceived legitimacy, trustworthiness, and obedience. The results of the SEM revealed that perceptions of legitimacy had both direct and indirect effects on intentions to support anti-doping policies. The effect of perceptions of legitimacy was mediated by social cognitive variables, which demonstrated strong direct effects on intentions. Importantly, the model was invariant across the countries, although mean differences in several constructs emerged. Conclusions: Anti-doping milieu and education impact athletes' willingness to support anti-doping policies. Interventions targeting legitimacy beliefs and social cognitive variables can be effective in promoting anti-doping policy support in competitive athletes. These interventions should expand beyond anti-doping policy legitimacy and target the specific beliefs (e.g., norms) that are pertinent to policy support in different countries. Highlights: Athletes receiving comprehensive ADE are more supportive of anti-doping policies than athletes who haven't received ADE. Anti-doping education can increase the legitimacy of authorities implementing anti-doping policies. Perceptions of legitimacy have both direct and indirect effects, through social cognitive variables, on intentions to support anti-doping policies. The effect of legitimacy perceptions on intentions to support anti-doping policies is invariant across the countries, but mean differences exist.